A Review Paper on New Trend in Green Technology (International Journal of Innovative Research in Engineering & Management, 2021)
The adaptation of science to human needs is technology.  Technology the current technological developments are  accelerating to the point that they can permanently harm our  planet. Every technology has advantages and disadvantages, but  they prefer to ignore the bad effects that are producing major  disruptions in human life and animal habitats. As a result, green  technology aims to protect the environment through the use of  never-ending natural energy. It also serves to minimize the effects  of atmospheric pollutant emissions by replacing trash with  renovated goods, which leads to greenery and greening. There are  just a few divisions. They all have no adverse effects and will thus  be learned by future generations. It is only because we damage  this world that we are accountable for rescuing. In addition to the  green technological advantages, this study shows value. Over  $100 billion was invested in 2007, setting new global records for  new renewable energy resources, industrial plants and research &  development. However, since renewable energy aspirations fall  behind practice due to the rapid rate of transformation in recent  years.
Keywords: Green Building; Green Energy; Green Technology; Pollution; Renewable Energy